Attack‐pattern discovery based enhanced trust model for secure routing in mobile ad‐hoc networks. (11th May 2016) - Jhaveri, Rutvij H.; Patel, Narendra M.
Summary: Multi‐hop routing in an open environment in the absence of well‐established infrastructure and centralized authority strives for trustworthiness and cooperation of nodes in a Mobile Ad‐hoc Network (MANET). There is no guarantee of secure and reliable delivery of packets when some internal nodes intentionally perform packet forwarding misbehavior by compromising the routing mechanism. In this paper, we address this issue with a trust‐model integrated with an attack pattern discovery technique. Extended from the Ad‐hoc On‐demand Distance Vector (AODV) routing protocol, we propose a trust‐based scheme founded on nodes' historical behaviors which adopts a pattern discovery mechanism in order to detect suspicious activities from the malevolent nodes before they start dropping data packets. We also present the detailed mode of operations of three distinct adversary models launching various kinds of packet forwarding misbehavior. Theoretical analysis and experimental results prove that the integration of a pattern discovery method with a trust‐based model provides earlier detection of adversaries which follow specific attack patterns and weakens their damaging effects on the network in comparison to a solitary trust‐based model. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The novel trust‐based scheme discovers packet dropping adversaries following certain attack patterns using a pattern discovery mechanism and other packet dropping adversaries using a trust model. The scheme identifies the adversaries following attack patterns earlier than a solitary trust model. The scheme shows remarkable improvement in packet delivery ratio and network throughput against distinct adversary models under various network conditions. Table VI. RREQ and RREP packet details for Figure6 (a). RQ1 RQ2 RQ3 RQ4 RQ5 RP1 RP2 RP3 RP4 RP5 Source ns n2 n1 n4 n5 n3 nd n4 n2 n6 Destination sequence number 20 20 20 20 20 24 26 26 26 30 Hop count 1 2 2 3 3 2 1 2 3 2 Table VII. Neighbor trust records at time t for Figure6 (a). Monitoring node‐ > monitored node ns‐> n2 n2‐> n3 n2‐> n4 ns‐> n1 n1‐> n5 n5‐> n6 Attack patterns No No No No No Yes DTVij (t) 0.15 0 .44 0.05 0.21 0.02 0.25 Recommendation Trusted Trusted Trusted Trusted Trusted Distrusted Overall Assessment Trusted Distrusted Trusted Trusted Trusted Distrusted